Comparison of Monopolar Electrosurgical Conization and the Loop Electrosurgical Excision Procedure in the Management of High-Grade Squamous Intraepithelial Lesion - Ding, Jun; Xu, Haiou; Xia, Lihua; Cao, Shanshan; Wu, Qing (Frontiers in Surgery, 2021)
Objectives: To compare the performance and outcome of high-grade squamous intraepithelial lesion(HSIL) treated by monopolar electrosurgical conization (MESC) or loop electrosurgical excision procedure(LEEP). Methods: This was a retrospective study included 554 patients identified by a biopsy of HSIL. We used either LEEP or MESC for cervical conization. The medical records of these patients were reviewed including the basic information, status of excision margin, cone depth, cone width, fragmentation, complication, the result of 6-month follow-up after conization and reproductive outcome. Results: Compared with MESC, LEEP had significantly higher rate of positive endocervical margin (3.77% vs 8.65%; P = 0.018), burn injury of margin (4.90% vs 10.38%; P = 0.016) and lower rate of adequate cone depth (83.40% vs 89.62%; P=0.034), and LEEP was significantly more likely to be fragmented (P=0.000). The rate of abnormal cervical cytology and positive high-risk HPV(hrHPV) was not significantly different between these 2 groups at 6 months after cervical conization. Conclusion: Both LEEP and MESC appeared equally clinical effective in the treatment of HSIL. MESC resulted in better pathological outcome about status of margin, tissue fragmentation, cone depth.